Internal Audit Decision Making and Belief Adjustment Model - Savira Yunitasari; Luciana Spica Almilia (Universitas Hayam Wuruk Perbanas, 2023)
This research aims to examine the disparities in audit choices between auditors who are exposed to positive news followed by negative news and those who are exposed to negative news followed by positive news. The investigation focuses on the End of Sequence presentation pattern as well as the lengths of information series (short and long). The study employed a mixed-design experimental approach, incorporating both between-subjects and within-subjects elements. The participants in the research comprised 124 undergraduate students from Accounting Hayam Wuruk Perbanas University. The results reveal that there is no distinction in audit decisions between participants who first receive positive news followed by negative news, and those who receive negative news followed by positive news in the End of Sequence presentation pattern. It also demonstrates that the arrangement of evidence (positive news followed by negative news or vice versa) and the length of information series (short or long) do not influence the decision-making of internal auditors in relation to the End of Sequence presentation pattern. Overall, the study findings refute the hypothesis proposed by Hogarth and Einhorn (1992) regarding the belief model revision, as they fail to support the notion that the End of Sequence presentation pattern induces primacy effects.